EspcTM: Kinetic Transition Network Based on Trajectory Mapping in Effective Energy Rescaling Space - Wang, Zhenyu; Zhou, Xin; Zuo, Guanghong (Frontiers in Molecular Biosciences, 2020)
The transition network provides a key to reveal the thermodynamic and kinetic properties of biomolecular systems. In this paper, we introduce a new method, named effective energy rescaling space trajectory mapping (EspcTM), to detect metastable states and construct transition networks based on the simulation trajectories of the complex biomolecular system. It mapped simulation trajectories into an orthogonal function space, whose bases were rescaled by effective energy, and clustered the interrelation between these trajectories to locate metastable states. By using the EspcTM method, we identified the metastable states and elucidated interstate transition kinetics of a Brownian particle and a dodecapeptide. It was also found that the scaling parameters of effective energy provided a clue to the dominating factors in dynamics. We believe that the EspcTM method is a useful tool for the studies of dynamics of the complex system, and may provide new insight into the understanding of thermodynamics and kinetics of biomolecular systems.